Cation Vacancy-Induced Ferromagnetism in Nanocrystalline CaTiO3 Plate - Sun, Li; Zhang, Yongjia; Ju, Lin; Shi, Changmin; Qin, Hongwei; Hu, Jifan (IEEE transactions on magnetics, 2014)
The nanocrystalline CaTiO 3 plates annealed at 1000 °C for 1 h present room temperature ferromagnetism (FM). The FM almost disappears when annealed at 1000 °C for 12 h. The reduction of FM for the nanocrystalline plates after vacuum annealing suggests that the room temperature FM of CaTiO 3 nanocrystalline plate originates from the cation vacancies. The results of the density functional theory calculation show that the stoichiometric CaTiO 3 is nonmagnetic and the neutral Ca vacancy may be responsible for the observed FM in CaTiO 3 . In addition, the magnetodielectric effect is also observed in ferromagnetic CaTiO 3 nanocrystalline plate.